STATUS GIZI DAN STATUS KESEHATAN SUKU BADUY - Faisal Anwar; Hadi Riyadi (Food and Nutrition Society of Indonesia, 2009)
The objectives of the study were: (1) To analyze the socio-economic and demographic characteristics of Baduy people; (2) To analyze the health status and nutritional status of Baduy people and its influential factors. This research is an explorative and descriptive study on the socio-cultural aspects of food system. The data were collected through a direct interview and discussion with respondents as well as a direct observation at the location of respondents. A sample size of 338 households was drawn from the population. To obtain the data on the cultural aspects, history and socio aspect of food, in-depth interviews was conducted with 19 key persons. The study was last for 12 months. In Outer Baduy, the factors significantly related to nutritional status are age, number of household size, income, nutritional knowledge, and wife’s ability to read. In Moslem Baduy, only age and income are related to the nutritional status of children. In Moslem Baduy and the Outer Baduy, the correlation between age and W/A or W/H is similar: namely, the higher the age, the lower would the Z-score for the W/A or W/H. The income is significantly correlated to the child nutritional status according to Z-score for W/A with a high correlation coefficient, that is, 0.61. This means that the higher the income, the higher would be the Z-score value for the W/A. The distribution of adults according to BMI classification in Outer Baduy it shows that 12.7% husbands and 17.6% wives are thin (wasted), while the overweight prevalence of the husbands is 2.4% and the wives 8.6%. This shows that Baduy women suffer from double nutrition problems (double burden). When the survey was carried out, 2.7% women were pregnant and still breastfeeding, the rest was neither pregnant nor breastfeeding.